1999
DOI: 10.2307/3579942
|View full text |Cite
|
Sign up to set email alerts
|

Proto-Oncogene mRNA Levels and Activities of Multiple Transcription Factors in C3H 10T 1/2 Murine Embryonic Fibroblasts Exposed to 835.62 and 847.74 MHz Cellular Phone Communication Frequency Radiation

Abstract: This study was designed to determine whether two differently modulated radiofrequencies of the type generally used in cellular phone communications could elicit a general stress response in a biological system. The two modulations and frequencies studied were a frequency-modulated continuous wave (FMCW) with a carrier frequency of 835.62 MHz and a code division multiple-access (CDMA) modulation centered on 847.74 MHz. Changes in proto-oncogene expression, determined by measuring Fos, Jun, and Myc mRNA levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
2

Year Published

2002
2002
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 20 publications
3
36
2
Order By: Relevance
“…However, despite this general conviction that microwaves are not sufficiently energetic to be able to directly damage DNA, there is considerable evidence indicating that microwaves can be directly and indirectly clastogenic, with a significant increase in chromosome damage (Sagripanti and Swicord, 1986;Garaj-Vrhovac et al, 1991, 1992Maes et al 1993;Haidler et al, 1994;Sarkar et al, 1994;Singh 1995, 1996;Timchenko and Ianchevskaia, 1995;Balode, 1996;Verschaeve et al, 1994;Vijayalaxmi et al, 1997;Phillips et al, 1998;Tice et al, 1999). In addition, cell phone radiation can alter protooncogene activity (Ivaschuk et al, 1997;Goswami et al, 1999). However, a similar number of studies have failed to detect obvious clastogenic effects following microwave irradiation of isolated animal cells in vitro (Alam et al, 1978;Lloyd et al, 1984Lloyd et al, , 1986Wolff et al, 1985;Meltz et al, 1987Meltz et al, , 1989Meltz et al, , 1990Kerbacher et al, 1990;Maes et al, 1997Maes et al, , 2001.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite this general conviction that microwaves are not sufficiently energetic to be able to directly damage DNA, there is considerable evidence indicating that microwaves can be directly and indirectly clastogenic, with a significant increase in chromosome damage (Sagripanti and Swicord, 1986;Garaj-Vrhovac et al, 1991, 1992Maes et al 1993;Haidler et al, 1994;Sarkar et al, 1994;Singh 1995, 1996;Timchenko and Ianchevskaia, 1995;Balode, 1996;Verschaeve et al, 1994;Vijayalaxmi et al, 1997;Phillips et al, 1998;Tice et al, 1999). In addition, cell phone radiation can alter protooncogene activity (Ivaschuk et al, 1997;Goswami et al, 1999). However, a similar number of studies have failed to detect obvious clastogenic effects following microwave irradiation of isolated animal cells in vitro (Alam et al, 1978;Lloyd et al, 1984Lloyd et al, , 1986Wolff et al, 1985;Meltz et al, 1987Meltz et al, , 1989Meltz et al, , 1990Kerbacher et al, 1990;Maes et al, 1997Maes et al, , 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Results from, respectively, low intensity RFR (at the order of <1 W/kg) on experimental models in vivo are currently not available in the literature. Comparable studies on cells in culture have shown that nonthermal GSM-like RFR may induce increased c-fos expression [Goswami et al, 1999], without significantly interfering with cell proliferation [Higashikubo et al, 2001]. Our data on aberrant BMP related gene expression and localization in the rat newborn kidney provide evidence of persistent changes at the molecular level that can be ascribed to GSM-like RFR.…”
Section: Discussionmentioning
confidence: 54%
“…There are currently no data on the influence of GSM-like RFR on the regulation of gene expression during intrauterine rat development and any attempt for such interpretations would be speculative. Nevertheless, increased c-fos expression as a GSM-like RFR effect has been shown by two independent studies on different models, either transiently in vivo in the rat brain [Fritze et al, 1997], or in mouse fibroblasts in transit from the exponential to the plateau phase [Goswami et al, 1999]. The immediate early response gene c-fos, with c-jun as a heteromer, is important for the expression and autoregulation of BMP-4 during early organogenesis in Xenopus [Knochel et al, 2000].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Otherwise, no effects have been obtained on cell cycle, enzyme activity, gene expression, DNA and chromosome damage (Dutta et al, 1992;Cleary et al 1996;Fritze et al, 1997;Malyapa et al, 1997;Pentafield et al, 1997;Goswami et al, 1999;Bisht et al, 2002;Zeni et al, 2003). A wide range of studies in vivo was also conducted.…”
Section: Introductionmentioning
confidence: 99%